HMGB1 is associated with atherosclerotic plaque composition and burden in patients with stable coronary artery disease - Andrassy, Martin; Volz, Hans Christian; Schüssler, Alena; Gitsioudis, Gitsios; Hofmann, Nina; Laohachewin, Danai; Wienbrandt, Alexandra; Kaya, Ziya; Bierhaus, Angelika; Giannitsis, Evangelos; Katus, Hugo; Korosoglou, Grigorios (PLOS ONE, 2012)
OBJECTIVES: The role of inflammation in atherosclerosis is widely appreciated. High mobility group box 1 (HMGB1), an injury-associated molecular pattern molecule acting as a mediator of inflammation, has recently been implicated in the development of atherosclerosis. In this study, we sought to investigate the association of plasma HMGB1 with coronary plaque composition in patients with suspected or known coronary artery disease (CAD). DESIGN: HMGB1, high sensitive troponin T (hsTnT) and high sensitive C-reactive protein (hsCRP) were determined in 152 consecutive patients with suspected or known stable CAD who underwent clinically indicated 256-slice coronary computed tomography angiography (CCTA). Using CCTA, we assessed 1) coronary calcification, 2) non-calcified plaque burden and 3) the presence of vascular remodeling in areas of non-calcified plaques. RESULTS: Using univariate analysis, hsCRP, hsTnT and HMGB1 as well as age, and atherogenic risk factors were associated with non-calcified plaque burden (r=0.21, p=0.009; r=0.48, p<0.001 and r=0.34, p<0.001, respectively). By multivariate analysis, hsTnT and HMGB1 remained independent predictors of the non-calcified plaque burden (r=0.48, p<0.01 and r=0.34, p<0.001, respectively), whereas a non-significant trend was noticed for hs-CRP (r=0.21, p=0.07). By combining hsTnT and HMGB1, a high positive predictive value for the presence of non-calcified and remodeled plaque (96% and 77%, respectively) was noted in patients within the upper tertiles for both biomarkers, which surpassed the positive predictive value of each marker separately. CONCLUSIONS: In addition to hs-TnT, a well-established cardiovascular risk marker, HMGB1 is independently associated with non-calcified plaque burden in patients with stable CAD, while the predictive value of hs-CRP is lower. Complementary value was observed for hs-TnT and HMGB1 for the prediction of complex coronary plaque.